Correction: Li, et al. LncRNA NEAT1 Silenced miR-133b Promotes Migration and Invasion of Breast Cancer Cells. Int. J. Mol. Sci. 2019, 20, 3616 - Xinping Li (International Journal of Molecular Sciences, 2020)
The author wishes to make the following correction to this paper [...]